Perencanaan dan Perancangan Pusat Wisata Kuliner Laut di Serangan, Denpasar, Bali: bahasa indonesia - Anak Agung Ngurah Agung Candra Gupta; Made Suryanatha Prabawa; Ni Wayan Nurwarsih (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
The design of the Marine Culinary Tourism Center in Denpasar, Bali is the design of a tourist attraction that prioritizes culinary delights to attract the attention of foreign and domestic tourists, through the diversity of types of food provided visitors will be offered various culinary choices. The theme used is neo vernacular to support the emergence of local culture from this culinary tourism center building through a concept that is also supported by using local materials. Using the concept of eco living, landscape, distinctive architecture, biophilic design to create a harmonious blend of building architecture, nature and visitor comfort. Designing a culinary center tourism area that can meet the culinary needs of visitors and tourists in the city of Denpasar in terms of food and drink as well as a place of recreation and refreshment where visitors can enjoy various culinary tours that are able to reflect the culture and characteristics of Serangan, Denpasar City. This area is also accompanied by supporting facilities with an attractive architectural design besides that this design is also able to improve the economy of Denpasar City through culinary tourism facilities and city development as well as developing architectural works in Denpasar City.